Consumers’ Perception towards the Taxi Management in Kathmandu Valley: Awareness, Challenges, and Way-Forward - Devkota, Niranjan; Oli, Manish; Paudel, Udaya Raj; Parajuli, Seeprata (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
Taxi services are seen continuously growing throughout the globe. The service being able to cope with technological advancement has been benefitted to a greater extent. However, in Nepalese context taxi used in Kathmandu valley is still based on primitive technology and services still face several challenges. In this context, this research aims to examine consumers' perception of taxi management in Kathmandu valley. The study was carried out among 414 taxi users with the help of a structured questionnaire. The taxi users' awareness index is prepared to measure customers' awareness towards taxi management in Kathmandu valley. The data revealed that customers' awareness level regarding the taxi services in Kathmandu valley is moderate (43.5%) and still 21.8% of them are less aware. It is found that the majority (66.7%) have not faced any challenges while using taxi service and one-third (33.3%) have faced challenges - over price charge (93%), rude behaviors (89%), payment problem (64%), and communication problems are major ones. Such challenges are moderate and often occurred at night time and at office time. Respondents argued that taxi services can be managed by formulating proper rules and regulations by the government, online booking and payment systems, and the installation of GPS on taxis. These services would help to run the taxi service effectively in the valley.